Minimizing user and operator costs of single line bus service using operational strategies - Tang, Chunyan; Ceder, Avishai (Avi); Zhao, Shengchuan (Transport, 2018)
This work presents a methodology for minimizing costs involved in the operation of a single line bus service. The model developed is based on optimal implementation of operational strategies tailored to passenger demand for a bi-directional single bus line. As a result, the commonly used timetable for Full Route Operation (FRO) will have to change to accommodate three types of strategies: short turn, limited stop, and mixed strategy (a combination of short turn and limited stop). The use of operational strategies will better match supply and demand, and will thus improve operation efficiency. The optimization model determines which trips of the given FRO timetable will be implemented with given strategies considering the trade-offs between passenger and operator costs. Moreover, in applying the model, the availability of real time information for passengers is considered in the calculation of waiting times. The proposed model is interpreted in the context of a small example, which serves as an explanatory devise. Then, it is applied to a real life case study in Dalian, China. The results show an indication that a significant saving could be attained by the use of multiple strategies. These savings were especially observed in the reduction of operational costs involved with the saving of travel times and running empty seats.